Relationship between post partum depression with some demographic and ‎psychosocial factors in mothers visiting health - medical centers in city of Rasht - haydeh mahmoodi; naima khodadadi; noshaz mir haghjo; iman taghadosi (Guilan University of Medical Sciences, 2005)
Introduction: Postpartum depression is a kind of psychiatric disorder that demographic and ‎psychosocial factors are related to it. ‎ Objective: In this descriptive – co relational study that aimed to determine the rate of ‎postpartum depression and determine relationship between postpartum depression and ‎demographic and psychosocial factors. ‎ Methods: In this study ‎‏350‏‎ women were selected through random clustering. The instrument ‎for gathering data was two questionnaires including demographic psychosocial data and ‎Edinburgh test. Researcher through interview completed these questionnaires. ‎ Results: The result indicated that ‎‏16%‏‎ of sample had postpartum depression. The results ‎indicated a significant correlation between enough family income for expenditure (p< ‎‏0.0001‏‎) ‎satisfied living with husband relatives (p= ‎‏0‏‎.‎‏021‏‎) life unusual events (p<‎‏0.0001‏‎) history of ‎mental disorder in family (p<‎‏0.0001‏‎) history of post partum depression in family (p= ‎‏0.008‏‎) ‎unwanted pregnancy (p=‎‏0.041‏‎) wanted abortion (p<‎‏0.0001‏‎) satisfaction of mothers about ‎baby sex (p=‎‏0.034‏‎) satisfaction of husband family about baby sex (p=‎‏0.005‏‎) kind of ‎communication with husband (p<‎‏0.0001‏‎) kind of communication with husband family (p<‎‏0‏‎. ‎‏0001‏‎) and postpartum depression . There was not a significant relationship between age, ‎number of children, number of pregnancy and delivery, past abortion and still birth, ‎occupation condition, marital status, kind of delivery, level of education, the numbers of ‎members living in family, living with husband relative, kind of life unusual event, satisfied ‎husband about baby sex, satisfied husband about mother job, planning for care of new born ‎and post partum depression. ‎ Conclusion: Nurses have important roles in secondary prevention by screening women with ‎postpartum depression, and refer them appropriately and quickly to psychiatrist. Nurses need ‎to be knowledgeable about high – risk factors and share this information with women and ‎their families. ‎